JavaFX for dummies - Lowe, Doug (For Dummies, a Wiley brand, 2015)
JavaFX For Dummies gives you access to an innovativesoftware platform that allows you to create and deliver richInternet applications that can run across a wide variety ofconnected devices. This accessible book highlights the mostimportant features of this powerful graphics platform, giving youthe tools to understand it quickly and easily! No experience withJavaFX? No problem. JavaFX For Dummies has been writtenespecially for newbies and it also serves as a great referenceresource for more experienced Java developers